The phenomenological substance of voice and the deconstructional free play of writing in the philosophy of Derrida - Badleh, Jala (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Deconstructions to disrupt the transcendental signific trieation and its domination on the other implications by introducing a new concept: the concept of free play of the marque. This concept is based on the philosophy of the otherness and difference. Derrida never stooped to remind that the difference is not a concept or an idea or a term. We see the difference as Law, a Law of reading and writing. But it's also the Law of the Other and the different. It reflectsa philosophy of otherness that is rooted in the writings of Derrida. Derrida expressed this Law by a formulation that reduces deconstruction as a philosophy and as a method: tout autre est tout autre, a sentence that says the identity and the otherness together. It says the identity, and says the other, each other, the other in his irreducible plurality, the other "is" different and we cannot tell his identity. Peerless formulation of the Law that says the impossible.